Unveiling the influence of board dynamics and transparency on capital structure in the banking sector - Lestari, Devi; Rahmawati, Aryani Intan Endah (JIFA (Journal of Islamic Finance and Accounting), 2024)
Capital structure volatility in banking companies often stems from financial fraud, eroding public trust and leading to customer fund withdrawals. This study investigates the effects of board size, performance transparency, profitability, and company size on the capital structure of banking firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using purposive sampling, 181 data points were analyzed through multiple linear regression with EViews 10. The results reveal that board size, profitability, and company size significantly influence capital structure, while performance transparency shows no significant impact. These findings provide valuable insights for banking management in optimizing funding strategies and enhancing risk management practices. The study contributes to the broader understanding of how internal governance dimensions and company metrics shape capital structure decisions, offering practical guidance for enhancing corporate financial stability.